Analisis Pertimbangan Hakim dalam Putusan Onslag van Alle Rechtsvervolging atas Dasar Noodweer Exces (Studi Kasus Putusan Nomor: 125/Pid.B/2025/PN Lbo) - Tolhas J. F. Simanjuntak; Sonya Airini Batubara; Inez Lazuardi Karo Karo (Verdict: Journal of Law Science, 2026)
Indonesian criminal law adheres to the principle that punishment can only be imposed if the elements of a criminal act and the perpetrator's guilt are met. However, criminal law also recognizes a ground for exemption from punishment in the form of excessive self-defense (noodweer exces) as regulated in Article 49 paragraph (2) of KUHP. In criminal justice practice, noodweer exces is often used as the basis for imposing a verdict of onslag van alle rechtsvervolging. This research focuses on the judges' considerations in issuing the onslag van alle rechtsvervolging verdict based on noodweer exces, with a study on the Limboto District Court Decision Number 125/Pid.B/2025/PN Lbo. The problem formulation in this research is: How is the application of the noodweer exces provision as the basis for the onslag van alle rechtsvervolging decision in the practice of criminal justice in Indonesia? Second, how do judges consider the imposition of Onslag van Alle Rechtsvervolging based on excessive self-defense (Noodweer Exces) in the verdict? The study methodology utilized is normative legal investigation with a legislative, conceptual, and case approach. Legal materials were obtained thru library research and analysis of court decisions, and then qualitatively analyzed. The investigation findings show that the judge in Decision Number 125/Pid.B/2025/PN Lbo considered the existence of an unlawful attack, excessive self-defense, and severe emotional distress as a direct consequence of the attack. These considerations form the basis for the exoneration of the defendant, so that even tho the act was proven legally and convincingly, the defendant cannot be punished and is given a verdict of onslag van alle rechtsvervolging. Therefore, the decision reflects the application of noodweer exces as a mitigating reason in Indonesian criminal law.